(untitled) (Scientific journal of the Fergana State University, 2024)
This article describes the national roots of personnel training in the history of statehood and the development processes of the new system of personnel training in the field of public service in our country. At the same time, the content of political, legal and regulatory sources related to the formation of the system of public service personnel and the further improvement of their activity in our country was revealed, and proposals aimed at further improving the activities of public service personnel based on high responsibility and patriotism were also developed.